(untitled) (International Journal of Engineering and Computer Science, 2017)
Now-a-days there is a huge increase in usage of Online Social Networks (OSNs). But, these OSNs do not provide a security to the user walls against unwanted messages. Users can easily post any undesired contents on a user wall. This is a very important issue in OSN giving rise to misuse of these OSNs. Up to now OSN have provided little control regarding who can post on user’s private wall. Here we have proposed a system that will prevent unwanted messages from being posted on user’s wall. This can be done by scanning the messages for any undesired contents before they are being posted on any user wall. We have also proposed a Blacklisting mechanism which will block users frequently trying to post such messages and prevent them from further posting any messages on the user’s wall.